The evolution of sovereign debt default: From the thirteenth century to the modern era - Richard C. K. Burdekin; Richard J. Sweeney (The Journal of European Economic History (JEEH), 2021)
An examination of sovereign defaults over the long term, from 1294 to 2008, shows that serial defaults are far rarer than the much-ballyhooed experience of the 1980s suggests. the only mass default in Europe since 1294 took place in the early nineteenth century during the Napoleonic Wars. The majority of the serial defaults date from after 1975, primarily in Africa, Asia, and Latin America, and were heavily concentrated in the 1980s. These multiple defaults, like some earlier default waves in Latin America, reflected the experiences of newer nation states and were also linked to the inherent vulnerability of periphery countries to events in well-established, major financial centers. This was in sharp contrast to the earlier defaults in Eurpe and appears largely to be an aberration when viewed against the backdrop of the overall historical record.
Keywords: 330